The Influence of Perceived Ease and Risk of Use and Financial Literacy on Decisions to Make Transactions Using QRIS in SMES in South Denpasar - Ni Kadek Dhella Indri PUTRI; Putu Gede Wisnu Permana KAWISANA; I Nyoman SUTAPA (Journal of Tourism Economics and Policy, 2023)
This study aims to determine the influence of perceived ease of use and risk of use, and financial literacy on the decision to transact using QRIS on MSME (Micro small and Medium Enterprises) in South Denpasar. The population in this study is all MSME (Micro small and Medium Enterprises) in South Denpasar. The sample was determined using the Slovin formula, which obtained a sample of 99 MSME (Micro small and Medium Enterprises). The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that perceived ease of use has a positive and significant effect on the decision to transact using QRIS on MSME (Micro Small And Medium Enterprises) Â in South Denpasar, the risk of use has a positive and significant effect on the decision to transact using QRIS on MSME (Micro small and Medium Enterprises) in South Denpasar and financial literacy has a positive and significant effect on the decision to transact using QRIS on MSME (Micro Small And Medium Enterprises) in South Denpasar.